Experimental and numerical study on polymer grouting pretreatment technology in void and corroded concrete pipes. (July 2021) - Li, Bin; Wang, Fuming; Fang, Hongyuan; Yang, Kangjian; Zhang, Xijun; Ji, Yanting
Highlights: MBP-PGP technology was proposed and applied to a full-scale test. The mechanical behavior of concrete pipes with void and corrosion were investigated. The repair effect of MBP-PGP technology on the void pipes was revealed. Abstract: For old pipes that have been in service for a long time in disrepair conditions, it is common to find internal and external defects in the pipelines. The repair technologies for internal defects inside the pipes are well-established, but these technologies for the defects around the pipe are still in the early stage. In this study, an innovative trenchless pretreatment technology for concrete pipes with corrosion and void defects, termed as the membrane bag pile polymer grouting pretreatment (MBP-PGP) technology, was developed in the field test. As a part of this study, the circumferential strains and bending moments in the concrete pipes with the dense, repaired, and void beddings were investigated under different wheel loads. The observed data from the field test were validated by a refined three-dimensional (3D) finite element (FE) model. Furthermore, the impacts of different corrosion depths, corrosion widths, void depths, and void widths on the behavior of corroded pipes were also discussed. The results show that the values and distributions of the circumferential strains predicted by the FE model are similar to those observed in the test. When the wheel load was 83kN, the maximum increase of the strains and bending moment in the pipe with the void bedding was 63.3% and 54.0%, and that of the pipe repaired using the MBP-PGP technology was only 14.6% and 17.3%, respectively, compared to the pipe with the dense bedding. It can be concluded that the circumferential strains in the pipes with void and repaired beddings are positively correlated with the corrosion depth, void depth, and void width, while they are negatively correlated with the corrosion width.